Keamanan dan Efektivitas Analgesik pada Geriatrik: Peran Obat Konvensional dan Herbal - Kuswandi, Nabila; Andi Ulfiana Utari (Faculty of Pharmacy, University of Jember, 2026)
The increasing global geriatric population has led to a higher prevalence of chronic pain, particularly associated with musculoskeletal and degenerative conditions. Pain management in older adults is complex due to age-related physiological changes, comorbidities, and polypharmacy, which may increase the risk of adverse drug reactions. This review aims to evaluate the safety and effectiveness of conventional and herbal analgesics in geriatric patients. Conventional analgesics, including acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, and adjuvant therapies, remain the mainstay of pain management due to their proven efficacy. However, their use is often limited by potential adverse effects, especially gastrointestinal, renal, and cardiovascular complications, which are more pronounced in elderly populations. In recent years, herbal medicines such as curcumin (Curcuma longa), ginger (Zingiber officinale), and capsaicin (Capsicum annuum) have gained attention as alternative or complementary therapies. These agents exhibit anti-inflammatory and analgesic properties with relatively better safety profiles, particularly in mild to moderate pain conditions. Nevertheless, concerns regarding variability in active compounds, lack of standardization, and potential herb–drug interactions, including modulation of cytochrome P450 enzymes, remain significant challenges in clinical practice. In conclusion, an integrated and individualized approach combining conventional and herbal analgesics, guided by evidence-based practice, may optimize pain management outcomes in geriatric patients while minimizing risks.